2007
DOI: 10.1017/s026303460700002x
|View full text |Cite
|
Sign up to set email alerts
|

Research on the enhancement of power-load of two-cell SBS system by choosing different media or mixture medium

Abstract: In order to enhance the power-load of two-cell stimulated Brillouin scattering (SBS) system, methods of using different media and mixed medium are proposed. In theory, the amplification function of two-cell system of different medium with close vicinity in the Brillouin frequency shift (BFS) is analyzed. Also the variation of BFS of the mixed medium with the mixing ratio is analyzed. In the two-cell SBS system pumped by Q-switched Nd:YAG laser, the SBS system performance characteristics are investigated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Thus, the pre-pulse injection is introduced to preserve the SBS waveform and the effects of the pre-pulse injection are investigated for cross-type amplifier system with the SBS-PCMs. SBS has a broad range of applications especially SBS-PCMs have been discussed recently (Yoshida et al, 2007;Meister et al, 2007;Kong et al, 2007Kong et al, , 2006Kong et al, , 2005bKong et al, , 2005aKappe et al, 2007;Hasi et al, 2007;. SBS-PCMs give many advantages such as the natural compensation for the distorted beams, the easiness of the optical alignments, and so forth.…”
Section: Cross-type Amplifier System With Phase Conjugation Mirrors Fmentioning
confidence: 99%
“…Thus, the pre-pulse injection is introduced to preserve the SBS waveform and the effects of the pre-pulse injection are investigated for cross-type amplifier system with the SBS-PCMs. SBS has a broad range of applications especially SBS-PCMs have been discussed recently (Yoshida et al, 2007;Meister et al, 2007;Kong et al, 2007Kong et al, , 2006Kong et al, , 2005bKong et al, , 2005aKappe et al, 2007;Hasi et al, 2007;. SBS-PCMs give many advantages such as the natural compensation for the distorted beams, the easiness of the optical alignments, and so forth.…”
Section: Cross-type Amplifier System With Phase Conjugation Mirrors Fmentioning
confidence: 99%
“…In recent years, stimulated Brillouin scattering (SBS) has received considerable attention because it has a broad range of applications (Kong et al, 2007(Kong et al, , 2009Ostermeyer et al, 2008;Shi et al, 2008;Wang et al, 2007;Hasi et al, 2007Hasi et al, , 2008Meister et al, 2007;Yoshida et al, 2007). Especially, the Brillouin amplifier can amplify a weak signal with high gain (Glick & Sternklar, 1995;Bel'dyugin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve highgain amplification or enhance power load, Brillouin amplification in different media has been presented. Hasi et al (2007) reported that the power load of the generator cell was enhanced by using the amplifier medium with small absorption rate, and the generator medium with high optical breakdown threshold. According to the characteristic that the Brillouin shift of CS 2 is near to that of water, Gao et al (2008a) reported Brillouin amplification of weak Stokes signals from water, obtaining the signal gain of 10 8 for the signal energy of 1pJ by using CS 2 as the amplifier.…”
Section: Introductionmentioning
confidence: 99%
“…While most research regarding stimulated Brillouin scattering (SBS) has been focused on the characteristics of backscattered light for phase conjugation and laser pulse compression (Kong et al, 2007;Ostermeyer et al, 2008;Yoshida et al, 2007;Wang et al, 2007;Hasi et al, 2007), there are few studies as to the characteristics of transmitted light. When the pump intensity exceeds the SBS threshold, a strong SBS process takes place through the SBS medium, leading to a quick energy transfer from pump to the Stokes light, and accordingly an optical limiting characteristic in the transmitted light (Lu et al, 2006Hasi et al, 2008aHasi et al, , 2008b.…”
Section: Introductionmentioning
confidence: 99%